Predictors of health-related quality of life in children with chronic heart disease. (18th May 2017) - Niemitz, Mandy; Gunst, Diana C. M.; Hövels-Gürich, Hedwig H.; Hofbeck, Michael; Kaulitz, Renate; Galm, Christoph; Berger, Felix; Nagdyman, Nicole; Stiller, Brigitte; Borth-Bruhns, Thomas; Konzag, Ines; Balmer, Christian; et al.
Abstract: Objective: Chronic paediatric heart disease is often associated with residual symptoms, persisting functional restrictions, and late sequelae for psychosocial development. It is, therefore, increasingly important to evaluate the health-related quality of life of children and adolescents with chronic heart disease. The aim of this study was to determine medical and socio-demographic variables affecting health-related quality of life in school-aged children and adolescents with chronic heart disease. Patients and methods: The Pediatric Cardiac Quality of Life Inventory was administered to 375 children and adolescents and 386 parental caregivers. Medical information was obtained from the charts. The socio-demographic information was provided by the patients and caregivers. Results: Greater disease severity, low school attendance, current cardiac medication, current parental employment, uncertain or limited prognosis, history of connection to a heart–lung machine, number of nights spent in a hospital, and need for treatment in a paediatric aftercare clinic independently contributed to lower health-related quality of life (self-report: R 2 =0.41; proxy-report: R 2 =0.46). High correlations between self-reports and parent-proxy reports indicated concordance regarding the evaluation of a child's health-related quality of life. Conclusions: Beyond medical treatment, integration into school is important to increase health-related quality of life in children and adolescents surviving with chronic heart disease. Regular screening of health-related quality of life is recommended to identify patients with special needs.